2004
DOI: 10.1097/00000478-200404000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Grading Ovarian Serous Carcinoma Using a Two-Tier System

Abstract: In this study, we evaluate a two-tier system for grading ovarian serous carcinoma. This system is based primarily on the assessment of nuclear atypia with the mitotic rate used as a secondary feature. The study included 50 cases of low-grade ovarian serous carcinoma and 50 cases of high-grade ovarian serous carcinoma retrieved from the files of the Department of Pathology at the University of Texas M. D. Anderson Cancer Center from a 28-year period. Cases assigned to the low-grade category were characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
497
2
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 607 publications
(525 citation statements)
references
References 16 publications
19
497
2
7
Order By: Relevance
“…Tumors were classified into serous, clear cell, endometrioid, and mucinous types, and graded as low and high grade using The University of Texas M. D. Anderson Cancer Center criteria. 13 Cases were categorized as type I or type II based on histopathology review and Kurman models. 2 After evaluating each case, 2 tumor blocks from each case were selected, and tissue microarrays (TMAs) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Tumors were classified into serous, clear cell, endometrioid, and mucinous types, and graded as low and high grade using The University of Texas M. D. Anderson Cancer Center criteria. 13 Cases were categorized as type I or type II based on histopathology review and Kurman models. 2 After evaluating each case, 2 tumor blocks from each case were selected, and tissue microarrays (TMAs) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…Improvements in the understanding of the natural history and molecular pathology of serous carcinoma have demonstrated that HGSC and low-grade serous carcinoma are different tumour types with a different underlying pathogenesis and associated with different molecular events and prognosis. [40][41][42][43] Serous carcinomas are now classified as low-grade or high-grade and this has been endorsed by WHO 2014, 30 with the recognition that these are two different tumour types rather than low-grade and high-grade variants of the same tumour type.…”
Section: Tumour Gradementioning
confidence: 99%
“…[7,8] Malpicia et al, evaluated a two tier system based on well-defined morphologic features of nuclear atypia with the mitotic rate used as a secondary feature. [9,10] The IJBAR (2015) 6 (03) www.ssjournals.com two tier grading system was shown to be useful in predicting outcome and is also in line with current thinking on serous ovarian tumour pathogenesis. [8,11,12] This study was done to evaluate a two tier system for grading of ovarian serous carcinoma, as compared to the three tier system and to determine whether a predictive relationship exists between grade and survival.…”
Section: Introductionmentioning
confidence: 56%
“…The numerical values in the present study are in concordance with the study done by Malpicia with majority of high grade tumours being redistributed in grade 2 and grade 3 of Shimizu/Silverberg grading system and majority of the high grade cases showing a mitotic count of ≥12/10HPFs. [9] When survival was modelled using a proportional hazard model with the two grading system as predictors the p values for the two tier grading and Shimizu/Silverberg grading were p = IJBAR (2015) 6 (03) www.ssjournals.com 0.62 and p = 0.69 respectively, with neither grade having a significant predictive ability. This was not in concordance with the study by Malpiciain which, the pvalues for the two tier grading system and the Shimizu/Silverberg classification system were p= 0.02 and 0.24 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation